PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “SUSI: SUSUN SISI” PADA PEMBELAJARAN BANGUN DATAR - Kiky Ardhianti; Axcelleosa Gloria Setiawan; Ina Febrianti; Ika Santia (Afore : Jurnal Pendidikan Matematika, 2025)
This study was motivated by the low level of understanding among elementary school students, particularly those in fifth grade, regarding the topic of plane figures in mathematics. This condition highlights the need for innovative learning media that can enhance students’ active participation in the learning process. The primary objective of this research is to develop an interactive learning medium called SUSI (Susun Sisi), specifically designed to facilitate students’ comprehension of plane figure concepts in an engaging and accessible manner. The research adopts a Research and Development (R&D) approach using the ADDIE model, which includes five systematic phases: analysis, design, development, implementation, and evaluation. The study involved one instructional media expert and 30 fifth-grade students as research subjects. The instruments employed consisted of expert validation sheets and student response questionnaires. Data were collected through expert validation and limited trials with students, then analyzed quantitatively. The results indicate that the SUSI learning media was rated valid by experts with a score of 84%, and was perceived as highly practical by students, achieving a practicality rate of 93.14%. Therefore, the SUSI media is deemed suitable for use in mathematics instruction and is recommended for classroom implementation by educators.